THE THERAPEUTIC COMMUNITY AS A MODEL FOR SOCIAL REHABILITATION IN RESTORING THE SELF-CONFIDENCE OF RESIDENTS WHO USE ILLICIT DRUGS: A CASE STUDY OF THE JAKARTA CLASS IIA NARCOTICS CORRECTIONAL INSTITUTION - Putri, Syavira Desrania; Equatora, Muhammad Ali (Jurnal Kajian Pendidikan dan Psikologi, 2026)
Social rehabilitation is a process of restoring, developing, and rehabilitating an individual’s social functioning; this process is one of the approaches used in addressing drug-related issues, specifically Demand Reduction. The implementation of the Therapeutic Community method as a community-based therapy is carried out at the Class IIA Jakarta Drug Rehabilitation Center. This study employs a qualitative research approach. The objective of this study is to examine the implementation of the Therapeutic Community program and the restoration of residents’ social functioning in relation to their self-confidence. Essentially, humans require the support of others to effect change; the foundational theory of the Therapeutic Community draws upon behaviorism, which posits that individual change occurs through interactions with the environment, thereby leading to transformation within the individual. The Therapeutic Community applies the concept of a family, where each member bears responsibility for themselves and others—a principle known as “man help” or “mutual help.” In practice, the Therapeutic Community is guided by a counselor as a facilitator. Social functional recovery is also achieved through support from within the Therapeutic Community family and external support from families; these factors have a positive impact on the process of restoring residents’ self-confidence.